The Role of Peritoneal Dialysis in the Treatment of Acute Kidney Injury in Patients With Acute-on-Chronic Liver Failure: A Prospective Brazilian Study - Ponce, Daniela; Zamoner, Welder; Dias, Dayana Bitencourt; Pires da Rocha, Erica; Kojima, Christiane; Balbi, André Luís (Frontiers in Medicine, 2021)
This study aimed to explore the role of peritoneal dialysis (PD) in acute-on-chronic liver disease (ACLD) in relation to metabolic and fluid control and outcome. Fifty-three patients were treated by PD (prescribed Kt/V = 0.40/session), with a flexible catheter, tidal modality, using a cycler and lactate as a buffer. The mean age was 64.8 ± 13.4 years, model of end stage liver disease (MELD) was 31 ± 6, 58.5% were in the intensive care unit, 58.5% needed intravenous inotropic agents including terlepressin, 69.5% were on mechanical ventilation, alcoholic liver disease was the main cause of cirrhosis and the main dialysis indications were uremia and hypervolemia. Blood ureic nitrogen and creatinine levels sta¬bilised after four sessions at around 50 and 2.5 mg/dL, respectively. Negative fluid balance (FB) and ultrafiltration (UF) increased progressively and stabilised around 3.0 L and -2.7 L/day, respec¬tively. Weekly-delivered Kt/V was 2.7 ± 0.37, and 32.8% of patients died. Five factors met the criteria for inclusion in the multivariable analysis. Logistic regression identified as risk factors associated with Acute Kidney Injury (AKI) in ACLD patients: MELD (OR = 1.14, CI 95% = 1.09–2.16, p = 0.001), nephrotoxic AKI (OR = 0.79, CI 95% = 0.61–0.93, p = 0.02), mechanical ventilation (OR = 1.49, CI 95% = 1.14–2.97, p < 0.001) and positive fluid balance (FB) after two PD sessions (OR = 1.08, CI 95% = 1.03–1.91, p = 0.007). These factors were significantly associated with death. In conclusion, our study suggests that careful prescription may contribute to providing adequate treatment for most Acute-on-Chronic Liver Failure (ACLF) patients without contraindications for PD use, allowing adequate metabolic and fluid control, with no increase in the number of infectious or mechanical compli¬cations. MELD, mechanical complications and FB were factors associated with mortality, while nephrtoxic AKI was a protective factor. Further studies are needed to better investigate the role of PD in ACLF patients with AKI.